Colloid-Surface Characteristics and Amelioration Problems of Some Volcanic Soils in West Sumatra, Indonesia - Fiantis, Dian (2000)
Andisols from elevational transects at Mt. Marapi and Mt. Pasaman in West Sumatra, Indonesia were studied to characterize their physico-chemical and mineralogical properties. These soils are developed under audic, isothermic and isohyperthermic climatic regime. They have dark epipedons with high contents of organic carbon and low bulk densities « 0.9 Mg m-3). All the nine pedons studied were found to meet the physical and chemical criteria of andic materials. Major minerals in the sand fraction are quartz, plagioclase, hornblende, augite, hypersthene, olivine and volcanic glass. Some of the volcanic glass is coated with amorphous materials. Allophane, cristobalite, feldspars and halloysite are maj or minerals in the clay fraction. Some soils contain imogolite. Halloysite exists as tubular crystals. Gibbsite is found in Mt. Pasaman soils, while opaline silica is present in the surface horizons of Mt. Marapi soils.